Guia de orientações preventivas para saúde bucal da pessoa idosa - Vasconcelos, Ana Karina Moreira de (2019)
Introduction: the oral health status of the elderly is an indispensable and integral part of general health, being necessary its maintenance and prevention, because once compromissed can affect the nutrional level, the physical and mental well-being and diminish the pleasure of a active social living. Objectives: To search the literature on the relationship between oral health of the elderly with the quality of life and depression; to evaluate the oral health condition and its relationship with the quality of life and drepression of the elderly; Elaborate an orientation guide to the reality that the elderly present themselves. Methodology: This is a methodological study, with the following steps: systematic literature review to verify the relationship between oral health, depression and quality of life; field research with 120 independent elderly, performing oral health examination, general health, socio demographic questionnaire and applying the Whoquol Breef, Whoquol old, GDS-15 (Geriatric Depression Scale); structuring content according to search results for the elaboration of an Oral Health Orientation Guide in the elderly with preventive methods and relevant oral health guidelines.Results and Discussion: In the stage, we used the libraries and databases: Medline, Scopus, Web of Science, Lilacs, and Cochrane Library, in a comprehensive and unrestricted way to the year or language of publication. The MeSH terms used for search were: Elderly; Dental care for aged, Health services for the aged, (result) Depression, Quality of life. After screening, six studies were included which found that oral changes interfere with the quality of life and depression of independent elderly. In the second stage, a survey was conducted with the elderly in the city of João Pessoa (n= 120) who sought care in public and private services. Data were analyzed by Spearman correlation test and binary logistic regression model (a= 5%). Significant correlation was observed between the number of missing teeth and the physical (r = -0.180), enviroment ( r = -0.244), self-perceived health (r = -0.263) and score domains. WHOQOL-Breef total (r = -0,200). No correlation was found between the oral condition and the Geriatric Depression Scale. Logistic regression analysis showed that the largest number of missing teeth is related to the worst WHOQOL-Breef score (<75%) (PR = 1.07, 95% CI = 1.01-1.13). In addition, the elderly assisted in the public sector have a better WHOQOL-OLD score (> 75%) (PR = 0.54, 95% CI = 0.33-0.88), while women have a higher prevalence of depression (GDS). >5) (RP= 1.64, 95% CI = 1.05-2,59). Tooth loss impacts health-related quality of life, but has no relationship to depresssion in independent elderly. From the results, an Oral Health Guidance Guide was developed aimed at the elderly in order to implement and consolidate healthy oral hygiene habits that help in healthy aging and achieving a good quality of life. Conclusion: this study proposes the elaboration of a guide for the oral health control and prevention program of the elderly, contributing to a healthy aging and the maintaining a good quality of life.